A dynamic model of applicant faking. (May 2016) - Roulin, Nicolas; Krings, Franciska; Binggeli, Steve
In the past years, several authors have proposed theoretical models of faking at selection. Although these models greatly improved our understanding of applicant faking, they mostly offer static approaches. In contrast, we propose a model of applicant faking derived from signaling theory, which describes faking as a dynamic process driven by applicants' and organizations' adaptations in a competitive environment. We argue that faking depends on applicants' motivation and capacity to fake, which are determined by individual differences in skills, abilities, and stable attitudes, as well as by perceptions of the competition, but also on applicants' perceived opportunities versus risks to fake, which are contingent upon organizations' measures to increase the costs of faking. We further explain how selection outcomes can trigger adaptations of applicants, such as faking in subsequent selection encounters, and of organizations, such as changes in measures making faking costly for applicants in the long term.